The effect of malting on the crystallites and microstructure in Greek barley cultivar using x-ray diffraction and microscopic analysis - Adriana Skendi; Maria Papageorgiou; Efthimios Papastergiadis (Instituto Politécnico de Viseu, 2018)
Introduction: Malting was generally used to produce fermentable sugars from starch in order to permit alcoholic fermentation. Variation in the starch microstructure and crystallinity affects its water solubilisation as well as and its breakdown from the enzymes Objectives: The starch microstructure is explored in order to understand and possibly modify the malting process of a Greek barley variety if needed. To address the issue, a combination of microscopy and X-ray diffraction inspection methods were used to evaluate the variation of the starch granule morphology and the degree of crystallinity of starch. Methods: The effect of malting on the microstructure of barley starch was investigated for one Greek barley cultivar (Seirios). The barley seeds were provided from ELGO-DEMETER, Institute of Plant Breeding and Genetic Resources (Thessaloniki, Greece). The steeping was performed at 14°C (several soaking and aerating circles) until barley reached the desired moisture content. Then the steeped barley was allowed to germinate at 15°C. The germination was stopped by drying at 40-45°C for at least 20h (dry malt). The malt was obtained by kilning for 6 hours at 100°C. The barley, dry malt and malt were milled to pass through a 0.8mm screen before being analysed. Light microscopy photographs with Congo red staining were used to identify variation in the starch granule morphology. Moreover, the x-ray diffraction analysis of the barley meal, dry malt and malt millings were obtained. Finally, the analysis of X-ray diffractograms was performed in order to calculate relative crystallinity and the crystallite size of the starch. Results: The results demonstrated variations in the morphology of the starch granules. The stained light microscopy photographs revealed that the starch granules in barley were round, greater, smooth, and granular, and that of the dry malt and the malt appeared smaller and more elongated with scratches on the surface. The stained confocal microscopy photographs showed the beginning of the starch damage on the surface of the granules. X-Ray diffractographs revealed that the crystallinity of the barley starch was increased during dry malt production and then decreased during kilning but still remained greater than the native barley starch. Conclusions: Malting under the specified conditions, affected the morphology of the starch granules of Seirios variety as well as the crystallinity of the starch suggesting the partial degradation of the starch during steeping and germination as well as during kilning.